Hubungan antara peningkatan kadar immunoglobulin-e (IgE) dengan matrix metalloproteinase-9 (MMP-9) pada pasien sindrom koroner akut (SKA) di RSUP Sanglah, Denpasar, Bali - Anak Agung Yunda Prabundari; Ketut Suardamana; Ketut Suryana; Tjok Istri Anom Saturti (DiscoverSys Inc., 2020)
Introduction. Acute Coronary Syndrome (ACS) is a cardiovascular disease that has a high mortality rate. One of the markers which play a role in the pathophysiology of ACS is Immunoglobulin E (Ig E), one of the antibodies released by B lymphocytes as the result of complex interactions that can activate mast cells. Mast cells will activate Metalloproteinase-9 (MMP-9) then facilitate pathogenesis of acute myocardial infarction or acute coronary syndrome phase. This study aimed to determine the relationship between increasing levels of IgE and MMP-9 in ACS patients at Sanglah Hospital, Denpasar, Bali.Method. This was a cross-sectional analytic study, and the samples were collected from ACS patients at Sanglah Hospital, Denpasar, Bali, using a consecutive sampling method. A total of 73 samples were included in this study, then statistical tests and Pearson correlation test was conducted.Results. Seventy-three samples included in this study contain 59 men (80.8%) and 14 women (19.2%). The IgE level is between 0.5-1000 and MMP-9 levels between 6.91-29.56. There is a statistically significant correlation between IgE levels and MMP-9 levels in Acute Coronary Syndrome patients (p = 0.018: r = 0.277).Conclusion. We found a significant association between increased IgE and MMP-9 in patients with Acute Coronary Syndrome at RSUP Sanglah, Denpasar, Bali. Pendahuluan. Sindrom Koroner Akut (SKA) merupakan penyakit kardiovaskular dengan angka kematian yang sangat tinggi. Salah satu marker yang berperan dalam patofisiologi SKA adalah Immunoglobulin E (IgE). IgE merupakan salah satu antibodi yang dilepaskan oleh limfosit B sebagai interaksi kompleks yang dapat mengaktivasi sel mast. Sel mast yang sudah aktif akan mengaktivasi Metallopriteinase-9 (MMP-9) yang ikut berperan dalam patogenesis miokard infark akut atau sindrom koroner akut. Penelitian ini bertujuan unuk mengetahui hubungan peningkatan kadar IgE dan MMP-9 pasien SKA di RSUP Sanglah, Denpasar, Bali.Metode. Penelitian ini merupakan penelitian potong lintang analitik yang dilakukan pada populasi SKA di RSUP Sanglah, Denpasar, Bali. Sampel keseluruhan berjumlah 73 orang pasien SKA secara konsekutif diikutsertakan dalam penelitian ini, kemudian dilakukan uji statistik dan uji korelasi Pearson.Hasil. Dari hasil penelitian pada 73 sampel tersebut, didapatkan jumlah sampel 59 orang laki-laki (80,8%) dan 14 orang perempuan (19,2%). Adapun kadar IgE dalam rentang antara 0,5-1000 dan kadar MMP-9 antara 6,91-29,56. Terdapat korelasi yang bermakna antara kadar IgE dengan kadar MMP-9 pada pasien Sindrom Koroner Akut (p=0,018; r=0,277).Kesimpulan. Terdapat hubungan yang signifikan antara peningkatan kadar IgE dengan peningkatan kadar MMP-9 pada pasien Sindrom Koroner Akut di RSUP Sanglah, Denpasar, Bali.